Information Frictions, Global Capital Markets, and the Telegraph - Benjamin Wache (ZBW - Leibniz Information Centre for Economics, 2021)
Do information frictions have a causal impact on the international flow of financial capital? Using the international rollout of telegraph cables in the 19th century, I show causal evidence that reductions in information frictions had a significant and positive impact on the bilateral international flow of financial capital from the UK. For identification I use a geographic instrument, the ruggedness of the seabed. The effect of the telegraph is concentrated in capital flows to private recipients (and not distinguishable from zero for flows to public recipients), and particularly sizeable for flows to producers of tradeables (industrial firms and raw material producers). However, the telegraph also had a direct and sizeable impact on capital flows that was independent of the trade channel. Using data on newspaper mentions in the British press, I show that the mechanism through which the telegraph affected capital flows is partially captured by newspaper mentions.
Keywords: F3; G14; N2; N7; 330